Synthesis of Ag nano/TiO₂ material by gamma Co-60 ray irradiation method for dye-sensitized solar cell application - Nguyen Thi, Kim Lan; Nguyen , Ngoc Duy; Vo, Thanh Long; Nguyen, Thai Hoang; Vo Thi, Thu Nhu; Nguyen , Quoc Hien (Nuclear Science and Technology, 2016)
Silver nano deposited on TiO2 nano (Ag nano/TiO2) materials with different initial Ag+ content (0.1-0.75%, w/w) were synthesized by Co-60 gamma irradiation and used as photoanode of dye-sensitized solar cells. The characteristics of Ag nano/TiO2 were determined by X-ray diffraction (XRD), transmission electron microscope (TEM) and UV-visible spectroscopy (UV-Vis). Bandgap energy values of Ag nano/TiO2 materials were also determined. Ag nano/TiO2 has improved efficiency of solar-to-electrical energy conversion of solar cells. The efficiency of solar cell assembled with Ag nano 0.75%/TiO2 was of 4.71% which increased about 25.6% compared with that of the cell based on TiO2 (3.75%). Preparation of Ag nano/TiO2 material by gamma irradiation is promising method that may be applied on large scale for production of dye-sensitized solar cells and for other applications as well.